Sekolah Staf Dan Komando Angkatan Darat (SESKOAD): Doktrin Dan Implementasi Lewat Seminar Angkatan Darat 1965 – 1974 - Alwan Rachman (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
This reasearch discusses the history of the birth of the Army Staff and Command School (SESKOAD) and the development of curriculum and doctrine in 1965-1974. This research uses historical research methods. The sources used in this study are primary and secondary sources. Primary sources used in the form of archives, interviews, newspapers and periodicals. While the secondary sources used are books relating to the research theme. The Army Staff and Command School (SESKOAD) is a higher education institution in the Army. Its formation in 1951 was aimed at fulfilling the positions of officers and staff within the Army. The Army Staff and Command School also played a role in developing doctrines in the Army to the TNI. The tasks carried out by SESKOAD were important in the development of the TNI since its inception. The results of the study concluded that SESKOAD as an educational institution did not only play a role in the Army and TNI. Through the Army Seminar II organized by SESKOAD, the development of doctrine made an expansion in the role of the educational institution. The development of the New Order became one of the discussions in the Army Seminar II which emphasized the role of SESKOAD not only in the military field, but more broadly at the national level, especially in government.